Administration of Systemic Antibiotics for Dental Treatment in Kosovo Major Dental Clinics: A National Survey - Mustafa, Lirim; Islami, Hilmi; Sutej, Ivana (European Journal of Dentistry, 2022)
Objective Antibiotics misuse and a high level of antibiotics resistance is observed worldwide, but particularly in developing countries. Kosovo in the last decade is facing challenges regarding antimicrobial resistance. The purpose of the present study was to investigate patterns of antibiotics prescriptions of dentists in Kosovo's major dental clinics.Materials and Methods For Kosovo's prescribing pattern, data collection was obtained from 10 Regional Dental Clinics and a Tertiary Health Center regarding patients who were prescribed antibiotics in the years 2015 to 2019. Data analysis was performed by using descriptive statistics and was processed by using MS Excel.Results Most prescribed antibiotic during the observed period from 2015 to 2019 in Kosovo was amoxicillin, although a drastic increase of amoxicillin with clavulanic acid—as a broad-spectrum antibiotic—is observed. The trend of antibiotics use in tertiary health institutions is in an overall decrease in Kosovo with an exception in the year 2017. Despite this overall decrease, inconsistency in prescribing is observed when the pattern is analyzed for each region separately. The highest number of patients in health care dental clinics received antibiotics for maxilla-related health conditions and the lowest number of them for oncologic ones.Conclusion The patterns of antibiotics prescriptions by dental practitioners in Kosovo during the years 2015 to 2019 are fluctuating. Compared with the global health care standards, the irrational use of antibiotics in dental health care clinics in Kosovo still exist and this issue should be further addressed by respective actors.
Keywords: antibiotics; dentistry; resistance; prescriptions